EFEK PEMBERIAN JINTAN HITAM (Nigella sativa) TERHADAP GAMBARAN MAKROSKOPIS DAN MIKROSKOPIS ORGAN LAMBUNG Rattus norvegicus YANG DIINDUKSI ASPARTAM - Anggraini, Tiara; Sayekti, Fitria Diniah Janah (Bina Generasi : Jurnal Kesehatan, 2025)
Aspartame is an artificial sweetener that tastes 200 times sweeter than sucrose. Aspartame in the body is broken down into aspartic acid, phenylalanine, and methanol which accumulates in the blood then metnol will become formaldehyde Then formaldehyde enters the stomach cells, the ALDH enzyme will convert it into phosphomic acid, formic acid that comes out of the cell will inhibit mitochondrial respiration there is a decrease in ATP production which can increase lactic acid production because it accelerates the glycolysis process resulting in damage to the gastric mucosa. This study aims to determine the effect of giving black cumin (nigella sativa) on macroscopic and microscopic images of gastric organs rattus norvegicus induced by aspartame. This study is an experimental analytical research using 5 treatment groups including 1 normal group, 1 negative group and 3 aspartame and black cumin treatment groups where each group consists of 5 white rats and one reserve in each group. The results of macroscopic observations obtained the results of differences in gastric color where in groups (K0) and (K3) were pink while in groups (K1), (K2) and (K4) were white, had a chewy texture, and had different sizes for each group. In microscopic results analyzed using the One Way ANOVA statistical test, a signification value of <0.05 was obtained, which means that there is a significant difference in the average in all groups. Based on further Post Hoc Tukey tests, the most effective black cumin dose results provided a protective effect, namely the group (K3) with a dose of 0.2 mL / 200 g BB / day. .